Demographic and neonatal risk factors for childhood asthma in the USA. (4th March 2019) - Geier, David A.; Kern, Janet K.; Geier, Mark R.
Abstract: Objective: Asthma is the most common chronic condition diagnosed among children worldwide according to the World Health Organization (WHO). This study evaluated on a longitudinal basis prospectively collected medical records for demographic and neonatal information among United States (US) children diagnosed with childhood asthma in comparison to controls. Design: The Vaccine Safety Datalink (VSD) database was examined to identify cases ( n  = 5907) diagnosed with International Classification of Disease, ninth revision (ICD-9) healthcare provider diagnosed childhood asthma (493.xx) and controls ( n  = 11, 662). Patients: All cases and controls were health maintenance organization (HMO)-enrolled from birth until diagnosis or sufficient time to ensure that they were unlikely to receive a diagnosis, respectively. Main outcome measures: Child's gestational age in weeks at birth, birth weight in grams, maternal age in years at birth, Appearance-Pulse-Grimace-Activity-Respiration (APGAR) score at 1 minute and 5 minutes following birth, gender, and race. Results: The study results revealed childhood asthma was diagnosed significantly more frequently among males than females, and significantly more frequently among minority populations (Black > Hispanic > Native American > Asian) than White populations. Cases diagnosed with childhood asthma had significantly decreased mean values for the following neonatal risk factors: gestational age, maternal age, birth weight, and APGAR scores at 1 and 5 minutes following birth in comparison to controls. Conclusions: This study offers healthcare providers important demographic and neonatal factors significantly associated with childhood asthma, and should help aid in the early diagnosis and treatment of childhood asthma.